A new combination in Vachellia Wight & Arn. (Mimosaceae) - Deble, Leonardo Paz; Marchiori, José Newton Cardoso (Balduinia, 2014)
Acacia ibirocayensis Marchiori, species endemic in southwest of Rio Grande do Sul State is transferred to genus Vachellia. Description, illustration, comments about geographic distribution, conservation and allied taxa are furnished.